HUBUNGAN ANTARA KEPUASAN KERJA DENGAN MOTIVASI KERJA PADA KARYAWAN DI CV. X KOTA BANDUNG - Salman Muamal Hamidy; Pradiptya Septiyanti Putri; Nida Muthi Annisa (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
The purpose of this study is to determine the relationship between job satisfaction and work motivation on employees at CV. X city of Bandung. Respondents in this study were employees of CV. X city of Bandung, totaling 70 people (39 men and 31 women). The sampling technique used in this research is using a population study. The data collection method used a questionnaire which was presented in the form of a google form, using two measuring tools, namely a measuring tool for job satisfaction and a measuring tool for work motivation. The data analysis technique in this study uses product-moment correlation analysisBased on data analysis, there is a positive relationship between job satisfaction and work motivation on employees of CV. X city of Bandung. This means that if job satisfaction for employees is high, then work motivation for employees will also be high. Vice versa, if employee job satisfaction is low, then employee motivation will also be low.